2007
DOI: 10.1080/00365510701203488
|View full text |Cite
|
Sign up to set email alerts
|

Temporal changes of the plasma levels of cystatin C, β‐trace protein, β2‐microglobulin, urate and creatinine during pregnancy indicate continuous alterations in the renal filtration process

Abstract: The albumin levels decreased in the second and third trimesters, whereas the levels of chi2-macroglobulin were unchanged, which is compatible with a virtually unaltered transfer of chi2-macroglobulin between the intra- and extravascular space during pregnancy and a significantly increased extravascular fraction of albumin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
40
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 22 publications
6
40
1
Order By: Relevance
“…This was enhanced in patients with symptomatic dialysis-related amyloidosis (23). By contrast, SUr and SCr are distributed both in extracellular (both intra-and extravascular) and intracellular spaces (24), with presumed rapid equilibration between all three compartments during hemodialysis. It is presumed that small molecules are mostly affected by diffusive clearance and relatively unaltered by UF because of rapid equilibration.…”
Section: Discussionmentioning
confidence: 97%
“…This was enhanced in patients with symptomatic dialysis-related amyloidosis (23). By contrast, SUr and SCr are distributed both in extracellular (both intra-and extravascular) and intracellular spaces (24), with presumed rapid equilibration between all three compartments during hemodialysis. It is presumed that small molecules are mostly affected by diffusive clearance and relatively unaltered by UF because of rapid equilibration.…”
Section: Discussionmentioning
confidence: 97%
“…Creatinine is a small molecule compared to these peptides. It has been shown that there an increased filtration of small molecules like creatinine during pregnancy combined with a decreased filtration of medium-sized (10-30 kDa) molecules [35]. When bound to other molecules the size of the complexes will increase thus reducing the glomerular filtration.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our results, other groups have shown plasma β-trace levels to be unchanged until 36 weeks of gestation. 36,37) Thus, measurement of plasma L-PGDS in preeclamptic patients may reveal a difference from normal pregnant women, possibly allowing early diagnosis or prediction of preeclampsia.…”
Section: Discussionmentioning
confidence: 99%